Eksplorasi Etnomatematika pada Tari Tor-Tor Namora Pule di Deli Serdang - Nasution, Habib Al Ghifari; Lubis, Mara Samin (Media Pendidikan Matematika, 2025)
Mathematics is often considered foreign by students from everyday life. In this study, researchers explored the culture in the North Sumatra region, namely the culture of South Tapanuli. The culture is Tor-tor Namora Pule. This study aims to explore ethnomathematics in the Tor-Tor Namora Pule dance movement in Deli Serdang, which is related to flat geometry.The approach used in this research is an ethnographic approach, with qualitative research methods. Data obtained through interviews, the instrument in this study consisted of the main instrument, namely the researcher himself and auxiliary instruments in the form of interview guidelines. The data validity technique used is source triangulation. The results of the data analysis concluded that four main types of movements were identified in the Namora Pule dance, namely manyomba, mangido, manggolom, and manyomba which ended with the word horas. This study found ethnomathematical indicators related to the concept of flat geometry that are realized in these dance movements. The manyomba movement has the shape of a right triangle, an arbitrary triangle, and an obtuse triangle. The mangido movement shows a semicircle shape. Triangular and circular shapes are found in the manggolom movement. Finally, the manyomba/horas movement displays the shape of an isosceles triangle. This research indicates the integration of geometry concepts in the local cultural practice of Tor-Tor Namora Pule Dance, which has the potential to become a contextualized mathematics learning resource.